2010
DOI: 10.1370/afm.1038
|View full text |Cite
|
Sign up to set email alerts
|

Steroids as Adjuvant Therapy for Acute Pharyngitis in Ambulatory Patients: A Systematic Review

Abstract: PURPOSE This review summarizes the evidence regarding the effi cacy of adjuvant steroids for pain reduction in acute pharyngitis. METHODSWe searched for randomized controlled trials, using MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews, published between 1966 and December 2008. Two reviewers assessed the quality of each retrieved article and summarized the data. RESULTSOur review found 8 relevant randomized controlled trials (RCTs) with a total of 806 patients. There were 5 RCTs with adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…A 2008 systematic review of RCTs concerning the use of adjuvant corticosteroids in the treatment of acute pharyngitis was conducted. All eight RCTs included in the review reported statistically significant reductions in pain compared to placebo . Another systematic review of RCTs investigating the use of adjuvant corticosteroids after tonsillectomy also found statistically significant improvement in recovery with adjuvant steroids .…”
Section: Discussionsupporting
confidence: 69%
“…A 2008 systematic review of RCTs concerning the use of adjuvant corticosteroids in the treatment of acute pharyngitis was conducted. All eight RCTs included in the review reported statistically significant reductions in pain compared to placebo . Another systematic review of RCTs investigating the use of adjuvant corticosteroids after tonsillectomy also found statistically significant improvement in recovery with adjuvant steroids .…”
Section: Discussionsupporting
confidence: 69%
“…This has led some authors to suggest the universal use of corticosteroids in the treatment of AP, but systematic reviews or meta-analyses have shown that no definite conclusions can be drawn because some of the studies had methodological weaknesses in the way they assessed drug efficacy, and others did not adequately consider important characteristics of the enrolled patients or corticosteroid administration that may have influenced the results [8,[25][26][27]. Moreover, the advantage of corticosteroid use (i.e.…”
Section: Acute Pharyngitis (Ap)mentioning
confidence: 99%
“…Randomised control trials doi: 10.1136/bmj.j3887 | BMJ 2017;358:j3887 | the bmj suggest that a short course of low-to-moderate dose corticosteroids probably provides symptomatic benefit to patients with sore throat. [11][12][13][14] Despite this evidence, clinicians do not commonly use steroids. Reasons might include uncertain applicability of the evidence to patients with less severe disease, as the initial studies enrolled only patients with severe sore throat presenting to emergency departments, almost all of whom received antibiotics.…”
Section: Introductionmentioning
confidence: 99%